2018
DOI: 10.5463/dcid.v29i2.730
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for Wheelchair Users in Bangladesh: A Participatory Action Research Project

Abstract: Purpose: People who use wheelchairs face a range of physical, social, and economic barriers to regular participation in their communities. These barriers may be more acute in countries such as Bangladesh which are affected by poverty and often lack the physical infrastructure or resources necessary to create inclusive or accessible environments. This research aimed to identify: (a) the barriers and facilitators to accessibility faced by wheelchair users in Bangladesh; (b) how these barriers affect the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…4 )b. A study by Aldersey et al [ 47 ] revealed that wheelchair users seemed to face greater physical barriers to access to health services in cities. The results of the study of Rocha et al [ 43 ] from Fortaleza City in Brazil, revealed that more than 37% of people living with disability, face serious barriers in accessing health care services.…”
Section: Discussionmentioning
confidence: 99%
“…4 )b. A study by Aldersey et al [ 47 ] revealed that wheelchair users seemed to face greater physical barriers to access to health services in cities. The results of the study of Rocha et al [ 43 ] from Fortaleza City in Brazil, revealed that more than 37% of people living with disability, face serious barriers in accessing health care services.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-one percent of persons with traumatic SCI require a wheelchair for mobility and are considered to have a chronic disability (Islam et al, 2011). Research indicates that people with SCIs in Bangladesh rarely leave their homes, have few employment opportunities, are poor, and depend on family members (Aldersey et al, 2018). In addition, they tend to have long-term disability, high morbidity, are socially excluded, abused, and economically disadvantaged.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of financial resources and knowledge of proper care among persons with SCI, their families, and people in their communities, combined with a lack of affordable healthcare, largely contribute to this sad state of affairs [ 6 ]. Moreover, decreased social acceptance, increased stigma, and ongoing discrimination further impede persons with SCI in Bangladesh from achieving a good quality of life in society, and many lose their volition for social participation and their work lives [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%